STUDENTS’ DIFFICULTIES IN LISTENING COMPREHENSION AT SMP SWASTA KENANGA MEDAN - Elma Junita Pakpahan; Silvia Agatha Simbolon (UIN Alauddin Makassar, 2019)
Listening is the skill in learning English language, listening help us understand and master language skill and make learners easier to communicate in that language. Listening is a process to pay attention, understand, appreciate and interprete to get information by the speaker through spoken language. Listening comprehension includes the multiple processes involved in understanding and making sense of spoken language. The learners comprehend the messages being listened in the listening activity. Difficulties are condition where students can not listen very well, many factors influence this condition. The aim of this research is to find out students’ difficulties in Listening Comprehension at SMP Swasta Kenanga Medan and the English teacher solution in overcoming the difficulties that experienced by students. This research performed in SMP Swasta Kenanga Medan at eighth grade. Researchers used qualitative research design. The data collected by listening test, questionnaire and interviews. Based on students test result, from listening test researchers found that 9 from 14 students in eighth grade experienced difficulties in answering listening comprehension test, and the data from questionnaire showed most of students found difficulties when listening comprehension, especially in comprehending unfamiliar words, and the speed of the speaker when talking. From the interview among researchers with English teacher at eighth grade at SMP Swasta Kenanga Medan, the English teacher has some solutions such as students should listen to English songs, watch cartoon movies like ‘Finding Nemo’ etc. ABSTRAK Menyimak adalah keterampilan dalam belajar bahasa Inggris, Menyimak membantu kita untuk memahami dan menguasai keterampilan bahasa dan membuat pelajar lebih mudah untuk berkomunikasi dalam bahasa itu. Menyimak adalah proses untuk memperhatikan, memahami, menghargai, dan menafsirkan untuk mendapatkan informasi oleh pembicara melalui bahasa lisan. Menyimak mencakup berbagai proses yang terlibat dalam memahami dan memahami bahasa lisan. Pelajar memahami pesan yang didengarkan dalam kegiatan Menyimak. Kesulitan adalah suatu kondisi dimana siswa tidak dapat mendengarkan dengan baik. Tujuan penelitian ini adalah untuk mengetahui kesulitan siswa dalam Pemahaman Menyimak di SMP Swasta Kenanga Medan dan solusi guru bahasa Inggris dalam mengatasi kesulitan yang dialami oleh siswa. Penelitian ini dilakukan di SMP Swasta Kenanga Medan pada kelas delapan. Peneliti menggunakan desain penelitian kualitatif. data dikumpulkan dengan tes menyimak, kuesioner dan wawancara. Berdasarkan hasil tes siswa, dari tes menyimak peneliti menemukan bahwa 9 dari 14 siswa di kelas delapan mengalami kesulitan dalam menjawab tes menyimak, dan data dari kuesioner menunjukkan sebagian besar siswa menemukan kesulitan dalam Pemahaman Menyimak, terutama dalam memahami kosa kata asing, dan kecepatan pembicara ketika berbicara. Dari wawancara antara peneliti dengan guru bahasa Inggris di kelas delapan di SMP Swasta Kenanga Medan, solusi guru bahasa Inggris adalah: siswa harus mendengarkan lagu bahasa Inggris, menonton film kartun seperti 'Finding Nemo' dan film-film yang lain. Kata kunci: Kesulitan, Menyimak, Pemahaman, Solusi